The Effect of Using a PLTS Trainer Kit with IoT Control on the Competence to Build Smart Buildings - Anam, Moh Khoerul; Samsudi, Samsudi; Supraptono, Eko (Universitas Negeri Semarang, 2023)
This research aims to develop and analyze the feasibility and effectiveness of an Internet of Things (IoT)-controlled Solar Power Generator (PLTS) trainer kit. The research method employed is a quantitative approach using the Research and Development (RnD) method, following the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection is conducted through questionnaires and tests. Questionnaires are used to assess the suitability of the media by media experts and subject matter experts, while tests are used to measure student competence improvement before and after the treatment. The research results indicate that the PLTS trainer kit with IoT control has high feasibility, with a score of 87% from media experts and 88% from subject matter experts, categorizing it as highly feasible. The t-test results show a significant increase in student competence, with an average pre-test score of 58.4 and a post-test score of 76.16. Statistical analysis reveals a calculated t-value of -7.79 and a tabulated t-value of 2.00. Therefore, the null hypothesis (H0) is accepted, indicating a significant difference between the pre-test and post-test. As a recommendation, the researchers suggest that schools should provide adequate facilities for practical learning using the trainer kit. Furthermore, future research could focus on the development of IoT trainers, particularly within the SCADA system.